2014
DOI: 10.1111/ijd.12376
|View full text |Cite
|
Sign up to set email alerts
|

Skin dimples

Abstract: Skin dimples are a common occurrence in children. Besides being of cosmetic significance, they may give an important clue to an underlying genetic or metabolic problem. A simplified location-based algorithmic approach to diagnose the underlying cause of skin dimples is presented. Clinical significance of medically important dimples, especially sacral dimples, its association with occult spinal dysraphism, and a cost-effective diagnostic strategy for its imaging is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A smaller proportion of cases (10%) had definite interruption of fetal movement leading to generalized arthrogryposis, as noted in other studies (Moura da Silva et al, ; Sarno et al, ). Cutaneous dimples at the joints are known to occur when movements are decreased in arthrogryposis syndromes, leading to sustained positioning that favors the adherence of the skin to the bone (Kumar, Kanojia, & Saili, ). Even when mobility is normal at birth, dimples and abnormal foot and hand positions appear to reflect periods of decreased movement in utero.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller proportion of cases (10%) had definite interruption of fetal movement leading to generalized arthrogryposis, as noted in other studies (Moura da Silva et al, ; Sarno et al, ). Cutaneous dimples at the joints are known to occur when movements are decreased in arthrogryposis syndromes, leading to sustained positioning that favors the adherence of the skin to the bone (Kumar, Kanojia, & Saili, ). Even when mobility is normal at birth, dimples and abnormal foot and hand positions appear to reflect periods of decreased movement in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies have suggested that the risk of spinal malformations in asympto- matic, healthy infants with an isolated simple sacral dimple is exceedingly low [1]. Alongside this, several studies have suggested that there is little value in investigating a simple sacral dimple with further imaging [5], whilst others suggest simply performing a screening ultrasound scan [1]. Importantly, there is no clear guidance on an appropriate diagnostic workup in this group of children [1].…”
Section: Discussionmentioning
confidence: 99%
“…• [5]. Sacral dimples are the most commonly seen cutaneous anomalies on paediatric spinal examination [5].…”
Section: Relationship Between Sacral Dimples and Spinal Cord Malformamentioning
confidence: 99%
See 2 more Smart Citations